Unlocking the Secrets of Insects: The Role of Mass Spectrometry to Understand the Life of Insects - (:unkn) unknown (John Wiley & Sons, Inc., 2024)
Chemical signaling is crucial during the insect lifespan, significantly affecting their survival, reproduction, and ecological interactions. Unfortunately, most chemical signals insects use are impossible for humans to perceive directly. Hence, mass spec...
Keywords: Espectrometría de masas; Insectos